Factors Associated With Neurosyphilis in Patients With Syphilis Treatment Failure: A Retrospective Study of 165 HIV-Negative Patients - Cui, Wenying; Yan, Junling; Weng, Wenjia; Gao, Yanqing; Zhu, Wei (Frontiers in Medicine, 2022)
Background In recent years, the incidence of syphilis has increased year by year. Our study is to explore the risk factors for the development of neurosyphilis in patients who failed syphilis treatment. Methods A total number of 165 patients with complete medical records and who agreed to undergo lumbar puncture were divided into 47 neurosyphilis cases and 118 non-neurosyphilis cases according to the diagnostic criteria of neurosyphilis, and the differences in clinical characteristics and laboratory features between the two groups were analyzed. Significant variables were entered into multivariable logistic regression models. Results (1) There were statistical differences (p < 0.05) between the neurosyphilis (NS) group and the non-neurosyphilis (NNS) group in terms of the higher proportion of male and serum rapid plasma reagin (RPR) > 1:32 and the elevated cerebrospinal fluid white blood cell (CSF WBC) and CSF protein in the neurosyphilis group compared with the non-neurosyphilis group. (2) Male gender, serum RPR titers >1:32 at lumbar puncture, CSF WBC >8 × 106/L were significantly associated with neurosyphilis. Conclusion For patients who have failed syphilis treatment, lumbar puncture should be performed to exclude neurosyphilis, to enable early diagnosis and treatment, and to prevent irreversible damage of neurosyphilis, especially if the patient is male and has a serum RPR>1:32 and elevated CSF WBC at lumbar puncture, which are risk factors for neurosyphilis.